Clottability and Cross-Linking Reactivity of Fibrin(ogen) Following Differential Release of Fibrinopeptides A and B - Furlan, M; Seelich, T; Beck, E. A (Thrombosis and Haemostasis, 1976)
Human fibrinogen was treated at pH 6.0, 7.3 and 9.0 with thrombin, batroxobin (thrombinlike fraction of Bothrops atrox venom) or an extract of the venom from Ancistrodon contortrix contortrix. These three enzymes released the NH2-terminal fibrinopeptides A and B at different rates. Thrombin-free, preactivated factor XIII (factor XIIIa) was added to incubation mixtures to stabilize resulting fibrin(ogen) aggregates. Cross-linking of γ-chains and the size of covalently linked fibrin-fibrinogen oligomers were studied in an early stage of fibrinopeptide cleavage using polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulphate.Batroxobin (pH 7.3) and thrombin (pH. 6.0) preferentially released fibrinopeptide A, and resulting fibrin aggregates became rapidly insoluble. However, when fibrinopeptide B was removed with the contortrix enzyme, soluble cross-linked oligomers appeared initially. The opaque fibrin clots, produced by thrombin (pH 6.0) or contortrix procoagulant fraction (pH 7.3), were found to be devoid of α-polymers even after prolonged incubation with factor XIIIa. Our data suggest that the solubility and opacity of fibrin networks are not primarily related to the type of the cross-link (γ-γ versus α-α interactions).